Autologous Bone Marrow Transplant in Multiple Myeloma Patient With Bone Marrow Hematopoietic Stem Cell - D Santosa; Catharina Suharti; Edi Dharmana (Acta Medica Indonesiana)
Multiple myeloma (MM) is a malignancy with multiple complications such as recurrent bacterial infections, anemia, osteolytic lesions, bone marrow failure and decreased kidney function. In developed transplant center, the bone marrow transplant procedure is performed by the source of peripheral blood stem cells. Apheresis machine which is not always available in all Haematology and Oncology Centre in Indonesia, is required for harvesting stem cell from PBSC (peripheral blood stem cell). There are only a few reports on marrow-derived stem cells transplant from BM with a 24-hour storage in multiple myeloma cases. We report two cases with non-secretory myeloma stage III and IgG myeloma stage II (International Staging System). Both patients were treated with induction regimens CyBord until a complete remission. Once remission was achieved, an autologous bone marrow transplant procedures were performed. The source of haematopietic stem cells (HSCs) were harvested from bone marrow and stored for 24 hours at a temperature of 4◦ C. The complications were neutropenia, anemia, thrombocytopenia, mucositis, diarrhea, hair loss, and skin darkness. The HSCs grew well on day 12 and 23. After treatment in the isolation room, the patient’s condition improved and the patients were discharged.